Use of Direct Microwave Irradiation in the Synthesis of Vanadium Phosphorus Oxide Catalysts via Vanadyl Hydrogen Phosphate Sesquihydrate Precursor - Kang, Jo Yee; Leong, Loong Kong; Yap, Yeow Hong; Yong, Thian Khok (Indonesian Journal of Chemistry, 2024)
Four vanadyl pyrophosphate (VPO) catalysts were prepared via the sesquihydrate precursor route using direct microwave irradiation and reflux synthesis methods. The synthesis of the sesquihydrate precursor was carried out in 2 stages. The synthesized catalysts were denoted as VPOs-DD, VPOs-RR, VPOs-RD, and VPOs-DR; where VPOs represented VPO catalysts produced through sesquihydrate precursor, and D and R represented direct microwave irradiation and reflux synthesis methods, respectively. The direct microwave irradiation synthesis method was found to reduce the synthesis duration significantly for both stages of the precursor synthesis, from 48 to 4 h. An exclusive secondary configuration, akin to a needle-shaped form in chrysanthemums, is specifically noted in VPOs-DD could increase the specific surface area by 35.4% compared to the bulkier structure of VPOs catalyst produced via the conventional reflux synthesis method (VPOs-RR). Direct microwave irradiation could induce the removal of more than 4 times the total amount of oxygen atoms from the lattice of V4+ and V5+ phases, as compared to the conventional reflux method counterpart. This ultimately produced VPOs catalysts with greater catalytic performances and TON. In summary, employing direct microwave irradiation could generate VPOs catalysts with increased efficiency, improved activity and selectivity as compared to the conventional reflux method.